Estudo eletroquímico da oxidação de monóxido de carbono - Soares, João Tiago Teixeira (Brasil, 2020)
Fuel cells that use alcohol as fuel (DAFC) have been gaining a lot of prominence in recent years, because the flats are produced on a large scale. However, during the oxidation of these small organic molecules (methanol, ethanol), there is the formation of carbon monoxide, which is an intermediate that is strongly attached to the surface of the catalyst, causing the effect called poisoning. In this sense, it is imperative to study catalysts that are tolerant to CO. In this work, the electrochemical study of carbon monoxide oxidation in acid medium was carried out, using supported pt/C and Pt3Sn/C catalysts prepared by the Method of Formic Acid (MAF) and the cyclic voltammetry technique was used to verify catalytic activity in CO oxidation. The tests were performed in three stages: cyclic voltammetry in the gold electrode, cyclic voltammetry after the addition of the electrocatalysts, and cyclic voltammetry in the presence of CO. Through the cyclic voltamgram of the CO stripping, it was found that the beginning of carbon monoxide oxidation began in smaller potentials for Pt3Sn/C electrocatalyst, indicating better performance, because less positive oxidation onset potentials represent good activity and more tolerance to CO poisoning. In the adsorption potential of 50 mV, the values of the electrochemically active areas for the Pt/C and Pt3Sn/C electrocatalysts were 15.12 m2g-1 and 9.88 m2g-1 respectively, and these values were used for current normalization. The best adsorption potentials for carbon monoxide oxidation were 50 and 100 mV, as it was found in the second cycle that all adsorbed CO was oxidized. For the different adsorption times, a significant increase in the active area was noted, however, the highest active area value was to 10 min for both electrocatalysts, indicating that this is long enough for CO-saturated coating on the electrodic surface.